Developing Students’ Speaking Ability through Snowball Throwing Technique - Tini Mogea (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research is to prove whether the snowball throwing technique is effective or not in developing students’ speaking abilities at SMA Negeri 3 Ratahan. It is a pre-experimental design. The instrument used in collecting data is an oral test. The results show that the lowest pretest score was 4 and the highest posttest score was 10. Pretest scores totaled 137, while posttest scores totaled 181. The mean of the pretest scores was 5.95, while the mean of the posttest was 7.86. The standard deviation of the pretest was 0.46, while the posttest was 0.95. The pretest results show that the students are still struggling to learn the snowball throwing technique. The posttest results show that the students' proficiency in learning to speak through snowball throwing has increased.